LEVERAGING JAVANESE BATIK MOTIVES IN TEACHING NUMBER PATTERNS: THE PRELIMINARY PHASE IN ETHNO-REALISTIC MATHEMATICS EDUCATION APPROACH - Khasanah, Binti Anisaul; Prahmana, Rully Charitas Indra; Adiputra, Sofwan; Khalil, Ibrahim Alhussain; Pepkolaj, Lekë (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Traditional textiles, such as Javanese Batik in Indonesia, are not only cultural artifacts but also repositories of mathematical knowledge. While previous studies have explored the geometric transformations embedded in Batik motives, little attention has been paid to their numerical patterns and educational potential beyond geometry. Addressing this gap, the present study investigates the mathematical structures—particularly numerical patterns—and ethical values inherent in Javanese Batik motives. The novelty of this research lies in uncovering the integration of cultural heritage and mathematics through ethnomathematical analysis, which remains underexplored in existing literature. Utilizing an ethnographic approach, including literature review, documentation, and field observations, the study identifies recurring numerical patterns and embedded cultural philosophies within Batik designs. These findings reveal that Javanese Batik offers meaningful contexts not only for teaching mathematical concepts but also for fostering character education through values such as discipline, patience, and harmony. The results suggest that these motives can be transformed into culturally responsive teaching materials, particularly e-modules for learning numerical patterns. This study contributes to the broader field of mathematics education by demonstrating how local cultural artifacts can support cognitive and affective learning goals, thus offering a novel pathway for integrating mathematics with cultural and moral education.